226 Evaluation of a Low-Moisture, Molasses-Based Block Containing Organic Trace Minerals and a Saccharomyces Cerevisiae Fermentation Culture in Newly Weaned Beef Steer Calves. (12th April 2022) - Hamilton, Thomas G; Rusche, Warren C; Walker, Julie; Wright, Cody; Smith, Zachary K
Abstract: The objective of this study was to evaluate growth performance responses and hepatic trace mineral status of newly weaned steer calves offered a molasses-based "stress" tub. Steers [n = 46; body weight (BW) = 240; SEM = 1.0 kg) were used in a randomized complete block design experiment. On d -1 all steers were stratified by initial BW and allotted to pens (n = 4 to 5 steers per pen; 5 pens/treatment).Treatments were: 1) No "stress" tub (Con) or 2) Ad libitum access to a "stress" tub (Stress Tub; Purina Animal Nutrition, St. Louis, MO) for the first 21-d (Tub). Steers were allotted to their study pens within 36-h of weaning and the "stress" tub was introduced approximately 24-h post arrival. Tub disappearance was monitored daily. Liver biopsies (n = 2 steers/pen) were collected on d 7, 21, and 42 for determination of Co, Cu, Mn, and Zn. From d 1 to 21 and d 1 to 42 steers from in the Tub treatment consumed greater ( P ≤ 0.01) amounts of Co, Cu, Mn, and Zn. A treatment × day interaction for hepatic concentrations of Co ( P = 0.09), Cu ( P = 0.01), and Zn ( P = 0.01) were noted. On d 7, steers from Tub had greater (P≤0.01) hepatic Co, Cu, and Zn . On d 21, steers from Tub had greater ( P ≤ 0.01) hepatic Co and Cu. On d 42 steers from Tub had greater ( P = 0.01) hepatic concentrations of Cu. During the initial 21-d of the experiment gain efficiency was enhanced ( P = 0.03) by 25.0% in steers from Tub compared with Con. Cumulative ADG, DMI, dietary NE utilization, and G:F did not differ ( P ≥ 0.14). It is concluded that stress tubs do not influence overall growth performance or NE value of the diet during a 42-d period. Stress tub consumption increased hepatic mineral stores during the initial 21-d and enhanced Cu status of calves throughout the 42-d receiving period.